2004
DOI: 10.1089/fpd.2004.1.202
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Contaminated Feed in the Epidemiology and Control ofSalmonella entericain Pork Production

Abstract: Food animal producers have ethical obligations to reduce the risk of foodborne hazards in animals under their care. Contaminated feed is a recognized source of Salmonella infection of food animals and regulations to control Salmonella contamination of animal feed have existed in some countries for decades. The impact of reducing Salmonella contamination of animal feeds on the risk of human foodborne salmonellosis is difficult to assess, and is likely to vary among food animal industries. In the context of U.S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 76 publications
2
53
1
2
Order By: Relevance
“…Thus, in Europe, 9.1% of human Salmonella infections are caused by S. enterica serovar Typhimurium, with 21.4% of these infections being due to phage type DT104 (EFSA report for 2005 [see above]). Multidrug-resistant S. enterica serovar Typhimurium strains are found in pigs with particularly high frequency (15) and can be isolated from pork and pork products (7,21) (EFSA report for 2005 [see above]). In Germany, for example, 3.2% of samples taken from minced pork meat were Salmonella positive: 67% of these isolates were S. enterica serovar Typhimurium, and 69% of these were resistant to more than four antibiotics (EFSA report for 2005 [see above]).…”
mentioning
confidence: 99%
“…Thus, in Europe, 9.1% of human Salmonella infections are caused by S. enterica serovar Typhimurium, with 21.4% of these infections being due to phage type DT104 (EFSA report for 2005 [see above]). Multidrug-resistant S. enterica serovar Typhimurium strains are found in pigs with particularly high frequency (15) and can be isolated from pork and pork products (7,21) (EFSA report for 2005 [see above]). In Germany, for example, 3.2% of samples taken from minced pork meat were Salmonella positive: 67% of these isolates were S. enterica serovar Typhimurium, and 69% of these were resistant to more than four antibiotics (EFSA report for 2005 [see above]).…”
mentioning
confidence: 99%
“…Usually, in developed countries livestock is regularly monitored in order to estimate the prevalence of the pathogen and serovars and to perform control measures. Livestock can be infected with Salmonella by vertical transmission through infected parents or by horizontal transmission between animals, faeces, animal feed, or vehicles such as rodents or birds (Davies et al 2004). They are also widely distributed in cold-blood animals, especially in reptiles.…”
Section: Salmonella In Animal and Foodmentioning
confidence: 99%
“…Due to the complexity of its epidemiology and ecology, Salmonella control is a great challenge. As it has been proposed by Davies et al (2004) the food supply should be seen as a linear series of sectors engaged in production, harvest, distribution and consumption and the goal of control programmes is to define the optimal combination of interventions at each sector that delivers the maximum risk reduction at minimal cost. It has been demonstrated that the risk of Salmonella contamination increases across the pork production chain and reaches its maximum in the slaughterhouse (Duggan et al, 2010;Argüello et al, 2011a;Visscher et al, 2011).…”
Section: Salmonella Control In the Pork Production Chainmentioning
confidence: 99%
“…Several studies have demonstrated the relative low importance of feed as a primary source of infection to pigs (Harris et al, 1997). Salmonella is rarely detected after feed processing at the feed mills due to the thermal treatment coupled with good manufacturing practices, and moreover Salmonella serotypes sporadically isolated from feed are not related to those usually identified at the farm level (Harris et al, 1997;Davies et al, 2004;Torres et al, 2011). However, most researchers agree that feed can be easily contaminated at the farm level.…”
Section: Feeding Practices For Salmonella Control In Swine Farmsmentioning
confidence: 99%